Realization of the Implementation of Post-Divorce Child Support Obligations at the Purworejo Religious Court - Yuniar, Meli Dwi; Muhajir, Muhajir; Sudarmaji, Waluyo; Huda, Muhammad Chairul (Institut Agama Islam Negeri Kendari, 2024)
This research aims to find out how the implementation of child support obligations after divorce in the Purworejo Religious Court. And will also identify what factors influence it. The method used in this research uses a normative juridical approach. While this type of research is field research, which is taken from documents from the Purworejo Religious Court, direct observation and interviews with parties who have sued in court. The results showed that there are still many parents, especially fathers, who do not carry out their obligations in providing maintenance to their children. There are several influencing factors, including lack of legal awareness, lack of awareness of the obligations of a father, parents are too involved in the household, social factors and economic factors. Whereas the obligation to provide for children has been stated in the decision of the judge of the Purworejo Religious Court.